Electronic technologies during local elections: new challenges - Perezhniak, Boris; Karmazina, Catherine; Dudnyk, Ruslana; Solyannik, Kostiantyn; Severinova, Oleksandra (Cuestiones Políticas, 2020)
The COVID-19 pandemic poses new challenges, as no one can propresa will burst a new wave of morbidity. It is therefore worth thinking about the implementation of the electronic voting procedure. In view of this, it is important to explore the role of electronic technology in local elections, share it with the experience of several countries, as well as as analyse new opportunities for the transformation of the electoral process. The aim of the work is to study the role of electronic technologies during local elections. The subject of research is electronic technologies during local elections and social relationships that arise, change and end during the use of electronic processes during local elections. The research methodology combined a set of philosophical, general, and special approaches to scientific knowledge. A study of electronic technologies in local elections has shown that electronic technologies play an important role in electoral processes. It is concluded that, under modern conditions, it is important for Ukraine to support the electoral process with the latest electronic technologies, because these technologies, if used correctly, ensuring election democracy and greater the efficiency of democracy institutions represents.